Root canal treatment on the complex case using ultrasonics: a case report - Wibowo, L.H.; Elline, E.; Fibryanto, E.; Prahasti, A.E.; Zulkifly, Dinie Qurratuaini (CRC Press, 2024)
This is a complex case involving the management of a tooth with pulp stone and an S-shaped canal configuration. The pulp stone is a type of pulp calcification with prevalence of up to 50%. They can be found in either coronal, radicular, or both pulpal regions: and their presence may cause difficulty during access cavity. S-shaped canals may involve several curvatures, with maximal curvature in the apical third. These double-curved canals are usually identified radiographically in a mesiodistal direction. Mostly, S-shaped canals are found in maxillary lateral incisors, canines and premolars, and mandibular molars. A 27-year-old female presented with spontaneous pain for approximately two months. Clinical examination showed leaking existing temporary restorations on teeth #11 and #12. The radiographic examination showed that teeth #11 and #12 had fractures involving the pulp, with an S-shaped canal configuration on tooth 12 and pulp stones on tooth #11. The diagnoses for both teeth were irreversible pulpitis. Following the access cavity on tooth #11, the pulp stone was removed using ET8D ultrasonic tip. Meanwhile, for tooth #12, an S-shaped canal was encountered at the apical third, and stripping occurred at the inner curvature confirmed on the radiograph. Single-visit endodontic treatment was performed prior to direct composite restoration. Removal of pulp stone poses a challenge to the clinician during access cavity, while thorough cleaning and shaping of an S-shaped canal require high operator skill. A proper armamentarium as well as the usage of magnification is of paramount importance to avoid iatrogenic damages such as stripping/ledging of the root canal system.